Noble Metals in Arc Basaltic Magmas Worldwide: A Case Study of Modern and Pre-Historic Lavas of the Tolbachik Volcano, Kamchatka - Kutyrev, Anton; Zelenski, Michael; Nekrylov, Nikolai; Savelyev, Dmitry; Kontonikas-Charos, Alkiviadis; Kamenetsky, Vadim S. (Frontiers in Earth Science, 2021)
Platinum-group elements (PGE) and gold are a promising tool to assess the processes of mantle melting beneath the subduction zones. However, fractionation processes in magmas inevitably overwrite the initial metal budgets of magmas, making constraints on the melting processes inconclusive. Moreover, little is still known about the geochemical behavior of a particular metal in a single arc magmatic system, from mantle melting towards magma solidification. Here we compare noble metals in lavas from several eruptions of the Tolbachik volcano (Kamchatka arc) to better understand the effects of magma differentiation, estimate primary melt compositions and make constraints on the mantle melting. We show that Ir, Ru, Rh and, to a lesser extent, Pt are compatible during magmatic differentiation. The pronounced incompatible behavior of Cu and Pd, observed in Tolbachik magmas, rules out the significant influence of sulfide melts on the early magmatic evolution in this particular case. Gold is also incompatible during magmatic differentiation; however, its systematics can be affected by the inferred gold recycling in the plumbing system of Tolbachik. Although the Tolbachik lavas show only slightly higher PGE fractionation than in MORB, a notable negative Ru anomaly (higher Pt/Ru and Ir/Ru) is observed. We attribute this to be a result of greater oxidation in the subarc mantle (by 1 to 4 log units), which promotes crystallization of Ru-bearing phases such as Fe3+-rich Cr-spinel and laurite. The estimated Pd contents for the parental melt of the Tolbachik lavas approaches 6.5 ppb. This is several times higher than reported MORB values (1.5 ± 0.5 ppb), suggesting the enrichment of Pd in the mantle wedge. Our results highlight the influence of the subduction-related processes and mantle wedge refertilization on the noble metal budgets of arc magmas.